Research on dynamic characteristics of gas film of spherical hybrid gas bearings based on computational fluid dynamics - Jia, Chenhui; Cui, Zhiwu; Guo, Shijun; Ma, Wensuo (Canadian Society for Mechanical Engineering, 2019)
A realizable k–ε turbulence model for spherical spiral groove hybrid gas bearing films was established based on computational fluid dynamics (CFD). A six degrees of freedom passive grid was used to calculate the gas film pressure distribution, bearing capacity, and dynamic characteristic coefficients numerically. The gas flow field dynamic and static pressure coupling mechanism was studied. The effects of the rotation speed, gas film thickness eccentricity ratio, and gas supply pressure on the dynamic and static pressure bearing capacity, and dynamic characteristic coefficients during operation were analyzed as a method of research into the mechanical mechanisms of gas bearing stability. The CFD calculation analysis can simulate the complex gas flow in the transient flow field of the gas film and determine reasonable operation parameters to optimize the dynamic and static pressure coupling effects, which can improve the gas film bearing capacity, dynamic characteristics, and operational stability of gas bearings.
Keywords: dynamic characteristic coefficients; steady bearing performance; dynamic and static pressure coupling effects; gas film pressure distribution; six-degrees of freedom passive grid; gas bearing